Correlation of Principal's Managerial Competence to Teacher Performance in Wamena Papua - Hendrik Legi; Binur Panjaitan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Managerial competence is the ability to manage resources through planning, organizing, directing, and controlling activities to achieve organizational goals effectively and efficiently. The principal as a manager in educational institutions must have managerial competence of his teachers. The purpose of this study was to determine the correlation of principasl managerial competence on teacher performance. The method used in this study is a quantitative method. Quantitative problems more generally have large areas, complex levels of variation but are located on the surface. The research results obtained are a correlation between the principal’s managerial competence and teacher performance. The higher the managerial competence of a principal, the higher the teacher’s performance.